Tacky's revolt : the story of an Atlantic slave war - Brown, Vincent, 1967- (The Belknap Press of Harvard University Press, 2020)
"Tacky's revolt, in modern-day Jamaica, was the largest slave uprising in the eighteenth-century British Atlantic. A strikingly modern guerilla conflict, the revolt inspired both fear of and sympathy toward black lives. Vincent Brown offers a gripping account of the fighting and its reverberations across an interconnected world"--